Рассеяние электромагнитных волн в каналах коллайдера - Богомолов, Я.Л.; Юнаковский, А.Д. (Нелинейные граничные задачи, 2003)
The modern perspectives of linear accelerators for electrons and positrons are connected with high- frequency pumping. Therefore these structures need quasi-optical components. One possible variant of such a structure is an accelerator part of supercollider. It is presented as a periodic set of metal rings irradiated by a convergent quasi- cylindrical wave flux. The energy provided in such systems needs using the structure of periodic narrow channels with Bragg reflectors. In case of very narrow channels between the rings the problem of high precision manufacture occurs. Moreover, a discharge can appear. That is why the channels must be wide enough and contain a sequence of mutually phased irregularities. An optimization problem for this electrodynamical system of energy accumulation is considered. The aim is to achieve a homogeneous electric field of maximum amplitude in near axis domain. A structure period contains two distinct channels.